Directors’ Files, Isaiah Bowman - Stefansson, Vilhjalmur, 1879-1962; Bowman, Isaiah, 1878-1950 (1926)
Correspondence between Isaiah Bowman and Vilhjalmur Stefansson regarding his exploration of the North Pole